Endocrine and Metabolic Disorders in Bronchial Carcinoma. Issue 5734 (28th November 1970) - Azzopardi, J. G.; Freeman, E.; Poole, G.
Abstract : In an unselected series of 185 patients with histologically confirmed bronchial carcinoma 16 had endocrine disturbances attributable to the tumour (excluding pulmonary osteoarthropathy). Of these, 11 patients had hypercalcaemia; three inappropriate secretion of antidiuretic hormone; one Cushing's disease; three hypertrophic osteoarthropathy; and one gynaecomastia. Cushing's disease and inappropriate antidiuresis are specifically associated with oat-cell tumours, and hypercalcaemia occurs most frequently with squamous carcinoma. A negative correlation exists between gynaecomastia and osteoarthropathy on the one hand and oat-cell carcinoma on the other.